Design Of Bandpass FIR Digital Filter - Sahamir, Sheila Rita (Universiti Sains Malaysia, 2005)
This work is concerned with the design of digital bandpass FIR filter using three differents method; Window, Optimal and Frequency sampling. Besides, the filter will be designed using MATLAB Version 6.5.1 that available in the School of Electrical and Electronic, Engineering. The project then will compare the merit and de-merit of each method. The project also has a simple step-by-step guide for designing bandpass FIR digital filter. From the given specification, we will calculate the appropriate parameters that will be used in MATLAB programming. Basically, there are five steps involve in designing digital filter such as specification of the filter requirements, calculation of suitable filter coefficients, performs the suitable realization structure for the filter, analysis the effects of finite wordlength on the filter performance and implementation in software and/ or hardware. It has been found that the Optimal method of this design of FIR digital filter provides the best result as it produces filter which meet the specification with the least number of coefficient. The suitable filter realization will be used is transversal filter that is the most widely using in implementation of the digital filter.